Mystery behind dimensions- “revealing gender by Foramen Magnum ”- a study - Srivastava, Shilpi; Raina, Anudeep; Sunil, M K; Gupta, D.S. (Forensic imaging (Online), 2020)
Human identification is of vital significance to the society and one of the positive indicators for identity is gender. This research paper presents a database of morphometric variables of Foramen Magnum and Occipital Condyle and their significance in gender determination along with different shapes of foramen magnum. The aim of the study was to evaluate the dimensions and shapes of foramen magnum and occipital condyles as an aid in gender determination using computed tomographic (CT) images. The present study included 60 axial CT scans of which 30 were males and 30 were females in the age range of 20-70 year fulfilling the inclusion and exclusion criteria. The various radiological parameters of foramen magnum and occipital condyles of 60 subjects including 30 males and 30 females were observed and significant sexual dimorphic differences were observed in various metric variables of Foramen Magnum and Occipital Condyle which were considerably larger in male population. Discriminant function analysis revealed an accuracy of 80% for Foramen Magnum, 78.3% for Occipital Condyle and 88.3% for concomitant dimensions of Foramen Magnum and Occipital Condyle. This study is distinctive in that morphological variation of shapes of Foramen Magnum with respect to gender observed and certain different morphometric parameters which have been found to be statistically significant both for Foramen Magnum and Occipital Condyle have not been studied in the past. Hence, it can be concluded that morphometric evaluation of dimensions of Foramen Magnum and Occipital Condyle using recent and advanced radiological methods such as CT increases the accuracy of gender prediction.